Language Environment Control Management Strategy Center for Ma'had Al-Jamiah UIN Maulana Malik Ibrahim Malang - Moch. Nurhasan Ubaidillah; Nuril Mufidah (At-Ta'dib, 2022)
The purpose of this research is to find out the control management strategy in creating an Arabic-language environment, the implications of the Arabic-language environmental control management strategy and the solutions to problems inhibiting the creation of an Arabic-language environment that are applied at Mabna ar-Razi Ma'had Al-Jamiah Center, UIN Maulana Malik Ibrahim Malang. The type of research used is descriptive qualitative with data collection using observations of the progress of language activities in ma'had, interviews with musyrif (managers) of the language and mahasantri divisions, as well as documentation of these language activities. Data analysis techniques applied by researchers are data reduction, data presentation, and data verification. The findings of this study are a form of management strategy for controlling the language environment implemented at the Ma'had Al-Jamiah Center of UIN Maulana Malik Ibrahim Malang which uses an informal language environment, namely making the environment outside the classroom a place for students to practice Arabic language skills and when in class language lectures through language programs yaum al-faan al-lughowy (language arts day), sima'i wal tarjamah (listening and interpreting) and tazwidul mufradat (adding vocabulary). The solution to the obstacles to creating an Arabic-language environment is by holding language programs as activities, tightening discipline in language, coaching related to language for both educators and students, and ma'had managers should continue to add material and language learning resources, both study material on various books modern or classic.